Genetic diversity and novel combinations of G4P[19] and G9P[19] porcine rotavirus strains in Thailand - Saikruang W. (2014)
Several epidemiological studies reported the detection of rotavirus strains bearing unusual combinations of genetic background of human and porcine rotaviruses. This observation supports the hypothesis of interspecies transmission of rotaviruses in humans and pigs. The aims of this study were to investigate the genotypes and molecular characteristics of rotaviruses in piglets with diarrhea in several farms from two provinces in Thailand. A total of 207 fecal specimens collected from diarrheic piglets were screened for the presence of groups A, B, and C rotaviruses. Group A rotaviruses were detected in 41 out of 207 (19.8%) fecal specimens tested. A wide variety of G-P combination rotavirus strains were detected in this study. The G4P[6] was identified as the most prevalent genotype (39.0%), followed by G4P[23] (12.2%), G3P[23] (7.3%), G4P[19] (7.3%), G3P[6] (4.9%), G3P[13] (4.9%), G3P[19] (4.9%), G9P[13] (4.9%), G9P[19] (4.9%), G5P[6], and G5P[13] each of 2.4%. Furthermore, G5 and G9 in combinations with P-nontypeable strains were also found at each consisting of 2.4% (n= 1) of the collection. It was interesting to note that among diversified porcine rotavirus strains, novel combinations of G4P[19] and G9P[19] strains were detected for the first time in this study. Nucleotide sequences of VP4 and VP7 of these strains were closely related to human rotaviruses reported previously. The data implies that these porcine rotaviruses were probably generated in nature from the reassortment between the viruses of human and porcine origin. This study provides valuable epidemiological information and molecular characteristics of porcine rotaviruses circulating in piglets with diarrhea in northern Thailand. © 2012 Elsevier B.V.